Assessment of ecosystem services of a recreational urban green space hub for green infrastructure planning the case of Quezon City Memorial Circle - Jamitsho, Yeshey; Morales, Mark Anthony M. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
As the world urbanizes rapidly, humans are increasingly exposed to the effects of urban development. Degradation of ecosystem services like clean air, recreational services, etc. caused by the reduction of urban green spaces leading to an eventual decline in human well-being is the main issue in urban areas like Quezon City today. Lack of a system that integrates green infrastructures planning in the mainstream development process as well as the general perception of users and decision makers alike on the importance of ecosystem services to individuals and city's well-being are the main causes thereof. At this backdrop, this study was conceived to assess the ecosystem services provided by urban green spaces by using tools that entreats user's perception on the environment, social, and economic values of ecosystem services to generate inputs for an informed planning of green spaces that addresses societal needs for an enhanced human well-being. In conjunction with this, considering the multi scale property of a green infrastructure that germinates from a site-specific hub, a prominent recreational urban green space hub (Quezon City Memorial Circle) that encompasses all the traits of an efficient green infrastructure and is visited by users from all parts of the city was chosen and assessed for its ecosystem services. The result of the assessment indicates the need for urban green spaces to be planned with attributes such as connectivity, integration, social inclusion, multi-functionality, multi-scale approach, multi-object approach, and inter and trans-disciplinary approach instilled in the green infrastructure planning process. To this end, the study uses the inferred attributes to formulate plans, guidelines, and recommendation to mainstream green infrastructure planning in the context of Quezon City.
Thesis (M.S.Regional and Development Planning)--University of the Philippines Diliman
Keywords: Recreation areas -- Philippines -- Quezon Memorial Circle(Quezon City).; Public spaces -- Philippines -- Quezon Memorial Circle(Quezon City).; Urban planning -- Philippines -- Quezon Memorial Circle(Quezon City).; City planning -- Philippines -- Quezon Memorial Circle (Quezon City).